Effect of long-term wave climate variability on performance-based design of coastal structures - Yuksel, Y.; Yuksel, Z. T.; Sahin, C. (MICHIGAN STATE UNIV PRESS, 2020)
Coastal and port structures represent a large economic investment for society during their lifetime. Therefore, there is a need for proper coastal planning and management. In order to do that, wave and current loads must be considered by determining their level where the coastal structure should resist, otherwise they may suffer extensive damage due to these environmental loads. In this study, a new frame of performance design for coastal structures which includes climate change effects is discussed as a future design methodology. Performance-Based Design considers a coastal structure's performance determined by the amount of damage. In other words, the structure which is exposed to wave impacts should maintain its serviceability by limiting its damage, so that, its economic, operational, life-safety and environmental impacts are acceptable to the owner. The importance of this method is that it provides a possibility to the owners to work with the engineer in order to establish desired and acceptable levels of wave loads as the basis for a design. Also, it gives an opportunity to the engineer to design structures with their foreknown behavior against the design wave load levels. These performance objectives include two specifications; the hazard levels to which the structure is to be designed, and the permissible amount of damage when the structure is subjected to these hazard levels. This paper aims to explain the performance-based design methodology by giving the deformation-based reliability design for breakwaters and its applicability to the stability design. Since the methodology requires information on the extreme wave-height distribution near the design site, the effect of wave climate change on the performance-based design is investigated.
Keywords: performance levels; reliability; climate change; coastal planning; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources